2016
DOI: 10.18805/lr.v0iof.9431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of irrigation based on IW/CPE ratio and sulphur levels on yield and quality of gram (Cicer arietinum L.)

Abstract: A field experiment was carried out during rabi 2010-11 to study the growth, yield and quality of gram as influenced by irrigation and sulphur levels. Irrigation and sulphur have shown significant influence on growth, yield, quality, moisture extraction pattern and water use efficiency. Among four irrigation schedules, irrigation scheduled at 0.9 IW/CPE ratio recorded higher values for all the growth parameters at various stages, yield attributes, grain and stover yield, quality parameters as well as net return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The lesser grain yield under surface irrigation method might be due to excess soil moisture (28 %) which prolonged the vegetative period even after flowering resulted in reduction of seed yield. Such findings were earlier reported by Sheoran et al (2001) and Srinivasulu et al (2016).…”
Section: Grain Yieldsupporting
confidence: 90%
“…The lesser grain yield under surface irrigation method might be due to excess soil moisture (28 %) which prolonged the vegetative period even after flowering resulted in reduction of seed yield. Such findings were earlier reported by Sheoran et al (2001) and Srinivasulu et al (2016).…”
Section: Grain Yieldsupporting
confidence: 90%
“…Similar finding were also reported by Kaisher et al [37]; Patel et al (2010) and Singh [27,28] reported that combined application of S (20 kg ha -1 recorded significantly higher protein content over control. revealed that increase in S levels from 0 to 40 kg ha -1 significantly increased the protein content (23.92 and 24.07%) [41][42][43][44].…”
Section: Quality Of Chickpeamentioning
confidence: 99%